Variability in instructions for performance of nasopharyngeal swabs across Canada in the era of COVID-19 – what type of swab is actually being performed? - Nole M. Hiebert; Breanna Ashley Chen; Leigh J. Sowerby (Journal of Otolaryngology - Head and Neck Surgery, 2021)
Abstract Background The primary method of surveillance for the presence of SARS-CoV-2 is with nasopharyngeal swabs. Given the significant demand for nasopharyngeal swabs, a large number of previously untrained and unfamiliar staff are now performing this test. It was noted that there was significant heterogeneity in instructions for performing nasopharyngeal swabs in Canada, in contrast to the guidance provided by the Centers for Disease Control and Prevention (CDC), and the Pan American Health Organization (PAHO). The objective of this study was to review the instructions provided across Canada and contrast them to those of the CDC and PAHO. Methods A standard series of steps for nasopharyngeal swab performance was outlined based on the CDC, PAHO, and New England Journal of Medicine instructions. A comprehensive search was performed in August 2020 to identify nasopharyngeal swab guidelines provided by public health in the provinces and territories of Canada. Regional health authority guidance was also collected. Instructions provided were contrasted against the standardized steps. Results Instructions were identified for all provinces and territories, and for 81 regional health authorities. From the provincial and territorial guidelines, 10/13 (77%) cleared the nasal passages before swab insertion, 11/13 (85%) tilted the patient’s head back slightly, 12/13 (92%) inserted the swab parallel to the palate, but only 3/13 (23%) inserted the swab to at least a depth of two-thirds the distance between the patient’s nose and ear. A clear majority (81%) of regional health authority guidelines followed their respective provincial guidelines. For depth of insertion, Quebec provided a pictogram but no distance or technique for estimation. Six provinces and territories - Northwest Territories, Nunavut, Ontario, Saskatchewan, Prince Edward Island and Alberta - recommended 4 cm or one-half the distance from nostrils to ear. British Columbia and Manitoba recommended a 7 cm depth of insertion. Nova Scotia recommended one-half to two-thirds the distance from nose to ear. Lastly, Newfoundland, New Brunswick and the Yukon recommended an insertion from nose to the external ear canal. Conclusion There is significant heterogeneity in guidance for nasopharyngeal swab performance across Canada. The instructions provided by the majority of provinces and territories in Canada would not be effective in reaching the nasopharynx. Graphical abstract